Communicating with underserved audiences: Focus group findings from two studies testing messages with low-income Hispanic, African-American and White audiences. Issue 2 (5th June 2017) - Goodman, J. Robyn; Theis, Ryan; Shenkman, Elizabeth
Abstract : Purpose: The purpose of this research is to understand how low-income, ethnically diverse, Medicaid recipients read, interpret and use culturally tailored health communications, specifically health plan report cards and health intervention/wellness program recruitment materials. Design/methodology/approach: The paper reports two exploratory studies on message design. Researchers considered 12 focus groups for Study 1, consisting of 51 African-American, Hispanic and non-Hispanic White men and women who were enrolled in Medicaid and had a behavioral health diagnosis and a chronic disease. Researchers considered 22 focus groups for Study 2, consisting of 102 Hispanic, African-American and non-Hispanic White women enrolled in Medicaid. Findings: The paper provides qualitative insights into how underserved populations interpret the visual and verbal aspects of health communications. Key findings include problems with cultural tailoring and monetary incentives for health improvement program participation, message components that show respect and are more likely to be read, how visuals can expand verbal messages and provide symbolic models and specifics on the desired image content. Research limitations/implications: Because of the qualitative approach, the research results may lack generalizability. Thus, researchers suggest conducting quantitative studies to test these findings. Practical implications: The paper includes implications for the development of powerful verbal and visual messaging for underserved populations. Additionally, the findings suggest a need to include emotional response in health communication theories and to incorporate visual communication theories in message design studies. Originality/value: Research on health communication with underserved populations is limited, yet these populations have higher incidences of death and disability from disease. This paper fulfills a need to discover best health communication practices with underserved populations.